PERTANGGUNGJAWABAN PERUSAHAAN PENGANGKUT (JNE) TERHADAP KERUSAKAN BARANG SELAMA PROSES PENGANGKUTAN - Antonius Mario Pea Wukak; Redemtus Deferetin Paldo Pone; Meryana Susi Paula Bere; Stefanus Don Rade (Cross-border, 2023)
In the current Indonesian society, examples of parties that provide services to transport or deliver goods are JNE, J&T, TIKI, Ninja Expres, Pos Indonesia and many more parties engaged in this field. In matters of implementation related to the performance of the transport agent (JNE) there are various provisions that regulate how the work procedures of the transport agent, namely JNE in these provisions the service users or consumers are also given various forms of compensation or in the form of liability to service users. The purpose of this research is to find out who or which parties are engaged or provide services in transportation or delivery and to find out how the work procedures of transportation agents. In this study the method used is normative because the object of research is about how the process of shipping goods by JNE agents, how the form of liability of JNE agents to the sender or recipient, and how the form of agreement between the sender and the transport agent. In the shipping process, it cannot be denied that there is damage to the goods sent through the JNE agent. In this case, there is insurance and compensation for the goods. . Based on these activities, there will be a legal relationship between the two that is binding, namely the so-called rights and obligations. The rights and obligations between service users and service providers (JNE) have been explicitly conveyed at the time of the agreement, where one of the main rights of service users or consumers is to get comfort, security, and safety in consuming goods and services while their obligation is to pay shipping money and the right of service providers is to get paid for shipments that have been made while their obligation is to send goods or files safely to their destination or to the recipient. Based on the research that has been done, the researcher knows about how the types of services and stages of delivery of goods from JNE to the recipient, how the transport agent or the sender of the goods is responsible for damage or negligence if things go wrong and the procedures for agreement between the person or party sending the goods with the transport agent. From the results of the discussion above, it can be concluded that it is very important to know related to the provisions that should apply in the transportation / delivery activities.